The Effect of Religiosity on Juvenile Delinquency in Islamic Senior High School Tebing Tinggi - Andriati, Ayu; Oktaviani, Annisa (Effect : Jurnal Kajian Konseling, 2024)
The Effect of Religiosity on Juvenile Delinquency in Islamic Senior High School Tebing Tinggi